MinION sequencing of seafood in Singapore reveals creatively labelled flatfishes, confused roe, pig DNA in squid balls, and phantom crustaceans. (June 2020) - Ho, Jonathan K.I.; Puniamoorthy, Jayanthi; Srivathsan, Amrita; Meier, Rudolf
Abstract: Food mislabelling is a growing world-wide problem that can be addressed through the authentication of ingredients via techniques like mass spectrometry or DNA sequencing. However, unfortunately traditional DNA sequencing methods are slow, expensive, and require well-equipped laboratories. We here test whether these problems can be overcome through the use of Nanopore sequencing. We sequenced 92 single and 13 mixed-species samples purchased in Singapore. We successfully obtained DNA barcodes for 94% and 100% of the single- and mixed-species samples respectively by applying a bioinformatics pipeline that was optimised for this purpose. We find comparatively low levels of clear-cut mislabelling for single-species samples (7.6%), while the rates are higher for mixed-species samples (38.5%). The low rates for single-species samples are somewhat deceptive, however, because of the use of vague species names. With regard to the clearly mislabelled single-species products, higher-value products (e.g., prawn roe, wild-caught Atlantic salmon, halibut) are replaced with lower-value ingredients (e.g., fish roe, Pacific salmon, arrowtooth flounder) while more serious problems are observed for mixed-species samples. Cuttlefish and prawn balls repeatedly contained pig DNA and all but one of the mixed samples labelled as containing crustaceans ('crab', 'prawn', 'lobster') lacked a significant number of crustacean signals. We conclude that there is a need for more regular testing of seafood samples and suggest that due to speed and low-cost, MinION would be a good instrument for this purpose. We also emphasize the need for developing clearer labelling guidelines. Highlights: We develop DNA sequencing with MinION as a seafood authentication tool. Most of the >100 seafood samples from Singapore were correctly labelled. Exception 1 (single species products): lower value products replace higher value products. Exception 2 (mixed-species product): some contain ingredients not indicated (pig). Exception 3: (mixed-species product): some lack ingredients implied by product name.